Correlation of fine needle aspiration cytology and histopathology in the diagnosis of salivary gland lesions in a tertiary care hospital in the Southern part of Assam: a 2 year observational study - Tabassum, Musfika; Deka, Monoj Kumar; Khakhlari, Nitu Mani (International Journal of Research in Medical Sciences, 2019)
Background: Fine Needle Aspiration Cytology (FNAC) of the salivary gland is one of the most challenging in the field of cytopathology due to the wide spectrum of lesions. There is significant cytomorphologic diversity and overlap between many benign and malignant salivary gland tumours. Though FNAC is quite an effective tool for the diagnosis of salivary gland lesions, it has always been under scrutiny and histopathology continues to be the final method to establish a diagnosis. Methods: A total of 80 patients who presented with clinical diagnosis of salivary gland mass at the Department of Pathology, SMCH, Assam from August 2017 to August 2019 were included in the study. FNAC was performed in all the cases and the cytological findings were correlated with that of the histopathological findings (wherever possible). Results: The median age group of patients was in the range of 30-40 years (30%). 60 patients underwent surgical procedure and hence histopathological correlation could be done in these patients. Among the various diagnosis in FNAC, benign tumours constitute the majority with 36 cases (60%). The most commonly involved benign tumour was pleomorphic adenoma (27 cases). The overall sensitivity, specificity & diagnostic accuracy of FNAC were found to be 87.3%, 93.9% and 93.33% respectively. Conclusions: FNAC is a safe, reliable, time saving, cost-effective, convenient and accurate method and should be considered as one of the pivotal investigations in the evaluation of salivary gland lesions.